Gender cardiology: clinical and pathophysiological features of the course the main diseases in women - I. L. Davydkin; V. P. Kuzmin; I. A. Zolotovskaya; R. K. Hayretdinov; S. P. Krivova; O. A. Rubanenko (Евразийский Кардиологический Журнал, 2024)
Coronary heart disease is the leading cause of death for both women and men. Older women, when coronary heart disease first appears, have more comorbidities and usually complain of atypical symptoms. Mortality and hospitalization rates caused by acute myocardial infarction are higher for women. It should be noted that adherence to secondary prevention for women is lower.Female predominance has been noted in idiopathic pulmonary arterial hypertension (IPAH), hereditary pulmonary hypertension, and collagenosisassociated pulmonary arterial hypertension. However, according to the latest data of the European register COMPERA, gender differences disappear for elderly patients and for the patients having concomitant diseases. The more frequent occurrence of cardiomyopathies among women is considered. Peripartum cardiomyopathy associated with pregnancy and childbirth, and Takotsubo cardiomyopathy due to psychoemotional status, in particular a stressful situation, determines a woman's further prognosis. Arrythmias are explained by changes in hormonal status during pregnancy, menopause, or are associated with the onset of the underlying disease.Heart failure usually affects both sexes equally, with women more likely to suffer from HFpEF and men from HFrEF. The classic cardiovascular, gender, and social risk factors for cardiovascular disease and heart failure have a different meaning for women than for men. It is necessary to take into account the parameters for EchoCG diagnostics for women, since the size of the women heart is smaller.